Enhancement of flow boiling heat transfer in microchannel using micro-fin and micro-cavity surfaces. (November 2021) - Lin, Yuhao; Luo, Yang; Li, Wei; Minkowycz, W.J.
Highlights: A numerical investigation into the flow boiling process in a microchannel with a micro-structured surface was performed. Micro-fin, micro-cavity, and smooth surfaces with varying wettabilities were investigated. The enhancing effects and detailed mechanisms of micro-structured surfaces were revealed. Abstracts: Micro-structured surfaces have a significant impact on the flow boiling process in microchannels, but few numerical studies have been carried out due to their complex nature. In this study, the numerical investigation of flow boiling on micro-fin, micro-cavity, and smooth surfaces in a microchannel was conducted, with water serving as the working fluid. The volume-of-fluid (VOF) method, the phase change model, and solid-fluid thermal coupling were adopted in an OpenFOAM solver to perform the computation. The enhancing effects and detailed mechanisms of the micro-fin and micro-cavity surfaces on the heat transfer process are discussed, and the influences of wettability on these surfaces are investigated. With a contact angle of 60°, the heat transfer coefficient of the micro-fin surface was 61.92% larger, and the overall thermal resistance was 36.64% lower than that of a smooth surface, respectively. The confined bubbles on the micro-fin surface had a much smaller dryout area on the heated wall due to the capillary wetting effect. Moreover, the micro-fin surface with the rising nucleate bubbles can induce vortexes, which strengthens the convective heat transfer. As for the micro-cavity surface, it had a moderate heat transfer enhancement with a 17.16% larger heat transfer coefficient and a 13.55% lower thermal resistance when compared with a smooth surface. When the wettability of a heating surface is enhanced, the dryout area is minimized. Thus, the heat transfer performance of the smooth and micro-cavity surfaces is enhanced. The enhancement resulting from modified surface wettability has less of an effect on the micro-fin surface because the micro-fin array serves a similar function to minimize the dryout area.